(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Shiras, also known as Uttamanga is the most vital part of our body. In Ayurveda, Shiro rogas are restricted to pain or discomfort seen around cranial vault and not the disorders of brain as such. Headache is the most frequent and troublesome reason to seek medical help in our day to day life. Tension type headache is the most common, primary, most neglected and difficult to treat occurring in about three-quarters of the general population. They can range from the occasional mild headaches to daily disabling headaches in some cases. Current allopathic approach is highly limited in treating the disease with just pain killers, which again have lot of side effects. Holistic Ayurveda approach practically is found to yield very good results in the patients of headache. Vataja Shiroroga can be an apt classical correlation of Tension-type headache. Atiuccha bhashana, Vegadharana, Ratrijagarana, Upavasa and Shoka are the major causes of Vataja shirashula. Classical books of Ayurveda advocate the use of Snehana, Swedana, Navana nasya, Snaihika dhumapana and local Vatahara kriya like Lepa and Parisheka as main mode of treatment. Nasya is a special therapy in all Shalakya disorders and Goghrita is considered as best Vatahara dravya. Kushtadi Lepa is indicated in Vataja Shiroroga classically. In this study, Kushtadi shirolepa and Goghrita pratimarsha nasya is done in a 19 year old patient having typical symptoms, to access the overall efficacy. After 1 month of therapy, significant improvement was seen in the symptoms. Mild recurrence was seen post follow-up period.